RANCANGAN SISTEM INFORMASI DATA INVENTARIS PADA HOTEL PUNDI REZEKI JAMBI - Suana, Irma; -, Nilawati (LP2M Universitas Nurdin Hamzah, 2020)
Inventory is a form of recording carried out to determine the stock of goods. Like the inventory sistem of goods at the Hotel Pundi Rezeki, it is not yet computerized and well integrated, so that errors in information often occur especially in the data of goods. Problems like this will have an impact on reports that must be made that are related to payroll. The method used by the author in this research is to conduct observations, interviews, literature studies, field studies, information sistem design followed by the construction of information sistems. The results of this study are inventory information sistems at the Hotel Pundi Rezeki built using the Visual Basic Programming language, Microsoft Visual Studio 2008 as Program Editor and MySql as a database. Designing information sistems inventory of goods at the Hotel Pundi Rezeki can manage goods data and make reports. Keywords: Information Sistems, Payroll, Microsoft Visual Studio 2008, MySql